Analisis E-Service Quality Terhadap Online Repurchase Intention dengan E-Trust Sebagai Variabel Mediasi - Nurcahya Kamila, Adinda Sofie; Komariah, Kokom; Saori, Sopyan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
E-commerce service performance is very flexible, where users cannot ensure that the online store provides the best service (e-service quality), so this must be considered by every e-commerce because excellent service quality will increase user e-trust thereby creating online repurchase intention. The purpose of this study is to determine the effect of e-trust in mediating the relationship between e-service quality and online repurchase intention. The method used in this research is quantitative method with descriptive and verificative approach. The population in this study were residents of Sukabumi City with an age range of 15-49 years. The sample of this study amounted to 200 respondents who were then analyzed using SEM (Structural Equation Modeling) techniques with the help of IBM SPSS AMOS version 24. The results of data processing show that e-service quality has a significant effect on e-trust with a Critical Ratio (CR) value of 9.552> 1.65 (the value on the t-table for a significance level of 5% is 1.65). E-trust has a significant effect on online repurchase intention with a CR value of 4.021> 1.65 (the value on the t-table for a significance level of 5% is 1.65). And e-trust successfully mediates the relationship between e-service quality and online repurchase intention with a value of 2,954.